Research of the crosswind effect on the single-rotor helicopter unintentional yaw rotation - V. V. Efimov; V. A. Ivchin; K. O. Chernigin (Научный вестник МГТУ ГА)
During the operation of single-rotor helicopters, aviation accidents quite frequently occur in the form of an unintentional turn or even a yaw rotation, causing, as a rule, a ground collision. Numerous researchers of this problem consider the loss of helicopter tail-rotor effectiveness due to wind effects as one of its possible causes. There is even a special term – the Loss of Tail Rotor Effectiveness (LTE) in the foreign literature. Hence, this paper deals with an attempt to determine the capacity of an unintentional single-rotor helicopter yaw rotation occurrence due to wind effects (the impact of the main rotor on the tail rotor was not considered in this paper). To solve this issue, theoretical methods (analytical calculations and computational experiments) were used. To carry out analytical calculations and computational experiments, a mathematical model of the Mi-8MTV helicopter yaw rotation dynamics was developed, on the basis of which a software package integrating the LTE module (for modeling the dynamics of rotational yaw motion of the helicopter) and OGL (for helicopter motion visualization) was created. Analytical calculations revealed that the yaw angular acceleration value monitored in-flight during an unintentional rotation can manifest itself due to the tail rotor thrust loss in the vortex-ring state. But for the development of an unintentional rotation to angles and angular velocities recorded in real flights, that kind of tail rotor thrust loss should occur during the entire turn. In computational experiments using the mentioned above software package, conditions failed to be created for that kind of thrust loss during the entire turn. Consequently, those yaw angles and angular velocities, that occurred in flights, could not be reached. The tail rotor, when blown by the wind in the investigated range of wind velocities (from 1 to 20 m/s) does not lose its effectiveness to such an extent that an unintentional rotation cannot be stopped by means of the tail rotor.